Exploring AKAPs in visual signaling - Tomczak, Julia; Mackiewicz, Joanna; Lisek, Malwina; Kaluza, Aleksandra; Boczek, Tomasz (Frontiers in Molecular Neuroscience, 2024)
The complex nature of the retina demands well-organized signaling to uphold signal accuracy and avoid interference, a critical aspect in handling a variety of visual stimuli. A-kinase anchoring proteins (AKAPs), known for binding protein kinase A (PKA), contribute to the specificity and efficiency of retinal signaling. They play multifaceted roles in various retinal cell types, influencing photoreceptor sensitivity, neurotransmitter release in bipolar cells, and the integration of visual information in ganglion cells. AKAPs like AKAP79/150 and AKAP95 exhibit distinct subcellular localizations, impacting synaptic transmission and receptor sensitivity in photoreceptors and bipolar cells. Furthermore, AKAPs are involved in neuroprotective mechanisms and axonal degeneration, particularly in retinal ganglion cells. In particular, AKAP6 coordinates stress-specific signaling and promotes neuroprotection following optic nerve injury. As our review underscores the therapeutic potential of targeting AKAP signaling complexes for retinal neuroprotection and enhancement, it acknowledges challenges in developing selective drugs that target complex protein–protein interactions. Overall, this exploration of AKAPs provides valuable insights into the intricacies of retinal signaling, offering a foundation for understanding and potentially addressing retinal disorders.